Polymorphisms in STAT-4, IL-10, PSORS1C1, PTPN2 and MIR146A genes are associated differently with prognostic factors in Italian patients affected by rheumatoid arthritis. (2nd August 2016) - Ciccacci, C; Conigliaro, P; Perricone, C; Rufini, S; Triggianese, P; Politi, C; Novelli, G; Perricone, R; Borgiani, P
Summary: Rheumatoid arthritis (RA) is a systemic autoimmune disease resulting in chronic inflammation of the synovium and consequent cartilage and bone erosion. RA is associated strongly with the presence of rheumatoid factor (RF), and consists of clinical subsets of anti-citrullinated protein antibody (ACPA)-positive and -negative patients. This study was designed to evaluate whether relevant single nucleotide polymorphisms (SNPs) associated with RA and other autoimmune disorders are related to RF, ACPA and clinical phenotype in a cohort of biologic drugs naive Italian RA patients; 192 RA patients and 278 age-matched healthy controls were included. Clinical and laboratory data were registered. We analysed a total of 12 single nucleotide polymorphisms (SNPs) in signal transducer and activator of transcription-4 (STAT-4), interleukin (IL)-10, psoriasis susceptibility 1 candidate 1 (PSORS1C1), protein tyrosine phosphatase, non-receptor type 2 (PTPN2), endoplasmic reticulum aminopeptidase 1 (ERAP1), tumour necrosis factor receptor-associated 3 interacting protein 2 (TRAF3IP2) and microRNA 146a (MIR146A) genes by allelic discrimination assays. Case-control association studies and genotype/phenotype correlation analyses were performed. A higher risk to develop RA was observed for rs7574865 in the STAT-4 gene, while the rs1800872 in the IL-10 gene showed a protective effect. The presence of RF was associated significantly with rs1800872 variant in IL-10, while rs2910164 in MIR146A was protective. ACPA were associated significantly with rs7574865 in STAT-4. The SNP rs2233945 in the PSORS1C1 gene was protective regarding the presence of bone erosions, while rs2542151 in PTPN2 gene was associated with joint damage. Our results confirm that polymorphisms in STAT-4 and IL-10 genes confer susceptibility to RA. For the first time, we described that SNPs in PSORS1C1, PTPN2 and MIR146A genes were associated differently with a severe disease phenotype in terms of autoantibody status and radiographic damage in an Italian RA population. Graphical Abstract: